Sumbangan Konsentrasi terhadap Kecepatan Tendangan Pencak Silat - Ihsan, Nurul; Suwirman, Suwirman (Universitas Negeri Semarang, 2018)
This study aims to determine the contribution contribution to the speed of pencak silat kick. This research is a correlational research. The sample in this study is the martial arts atlet of Universitas Negeri Padang which amounted to 50 people with sampling random sampling technique. Instrument used in concentration data collection with great concentrations exercise, while the instrument speed kicks with Nurul Shark test. Data analysis technique with product moment correlational formula. Based on the analysis of concentration with kick speed obtained correlation coefficient r = 0.28 at signification level ? = 0,05 and dk = n - 2 obtained rtabel = 0,26. This indicates that Ho is rejected and Ha is accepted, meaning the hypothesis is accepted is true. Furthermore, to know the contribution of concentration to kicking speed sought through coefficient of determination (r2) = 7.82%.